A comprehensive study on Green׳s functions and boundary integral equations for 3D anisotropic thermomagnetoelectroelasticity. (March 2016) - Pasternak, Iaroslav; Pasternak, Roman; Sulym, Heorhiy
Abstract: The paper derives Somigliana type boundary integral equations for 3D thermomagnetoelectroelasticity of anisotropic solids. In the absence of distributed volume heat and body forces these equations contain only boundary integrals. Besides all of the obtained terms of integral equations are to be calculated in the real domain, which is advantageous to the known equations that can contain volume integrals or whose terms should be calculated in the mapped temperature domain. All kernels of the derived integral equations and the 3D thermomagnetoelectroelastic Green׳s function for a point heat are obtained explicitly based on the Radon transform technique. Verification of the obtained equations and fundamental solutions is provided.